Celestino Tarambana - Nunez, Marisa; Cabassa, Mariona (Pontevedra [Spain] : OQO Editora, 2005)
Cesestino spends his time sleeping under the stars, hugging the trees, and making cabins out of ice with his tiny companion Rosamunda, until the day when Rosamunda goes missing.
Keywords: Friendship -- Juvenile fiction; Eccentrics and eccentricities -- Juvenile fiction; Missing persons -- Juvenile fiction; Spanish language materials -- Juvenile fiction